A Phenomenological Diagnosis of the ProDuct-based Instruction in EFL’s Writing Class: Barriers and Strategies to Tackle - Rungwaraphong, Piyawan (International Journal of Language Education, 2021)
This paper presents a phenomenological diagnosis of the implementation of ProDuct-based Instruction (PDI) in EFL’s writing class in Thailand contexts. PDI is a new instructional method for teaching business English writing. Its key is in the products that are tangible and appeal to human senses; the product’s tangibility serves as a scaffold to help students generate ideas and stimulate analysis and interrogations. The study focused on the first phase of PDI, in which students were required to learn inductively, and was conducted to explore barriers that both the learners and the instructors encounter while learning inductively in the researcher’s PDI approach, and to discover possible solutions to tackle with those barriers. Participants were 3 Thai lecturers of English writing and 60 Thai students from three government universities in Thailand. Data was collected through vignettes, participant observations, and   students’ written texts. Results indicate three major barriers of implementing inductive phase of PDI in Thailand contexts, which include: students’ English reading and grammar skills; students’ inference skill; and teachers’ inductive teaching expertise. The study suggests solutions to tackle these barriers, which include creating a guided graphic organizer, providing formative assessment and feedback for the students, and organizing a PDI training for the teachers who want to adopt PDI in their profession.